HEURMENEUTIKA GENDER TEKS AL-QUR’AN DAN HADIS - Muammar A. Wahid; Barsihannor; Muhaemin (Sulesana, 2025)
This study aims to analyze the gender hermeneutics of the texts of the Qur'an and hadith. Islam does not eliminate biological differences or social roles completely, but gives equal respect to the efforts and responsibilities of each. In terms of rewards, deeds, and relationships with Allah, there is no higher between men and women; the only difference is their piety. The concept of gender in the hadith also emphasizes balance, justice, and respect for the rights of men and women, and emphasizes the noble position of both before Allah. The hadiths of the Prophet Muhammad SAW often emphasize that men and women have different roles and responsibilities, but both are equally important and must be treated with respect and justice. The concept of justice in Islam emphasizes fair treatment of both sexes, despite differences in roles. Islam teaches that men and women have the same dignity before Allah, although with different duties and responsibilities.